Aspectos técnicos, econômicos e sociais da produção de batata doce - Martins Filho, José Bonifácio (2021)
Divided into three chapters, this dissertation covers social, economic and technical aspects of sweet potato production. In chapter I, the objective was to evaluate the panorama of sweet potato production in the Ibiapaba-Ce mountains, the dynamics of growth of the amount produced, planted area and sweet potato yield in the nine municipalities that make up the microregion of Ibiapaba in the period were evaluated. from 2010 to 2019. A characterization of the sweet potato production system by family farmers was also carried out. During the decade studied, Ibiapaba jumped from a production of 7.9 tons to 79.8 tons, the planted area grew from 680 to 3,795 hectares, in the same period. The sweet potato production system in family farming is extensive, predominantly empirical practices and rudimentary techniques. Chapter two evaluated the yield of sweet potato subjected to different levels of fertilization (NPK) associated with different concentrations of growth regulator (RC). A randomized block experiment was carried out in a 5 x 5 factorial scheme, with 5 levels of NPK (0 ; 696; 1044; 1392 and 1740 kg ha-1) combined with 5 concentrations of RC (0; 20; 25; 30 and 35 mL L-1). The number of total and commercial roots is influenced by the tested inputs and increases linearly with increasing doses and concentrations tested. The estimated maximum yield of sweet potato is 43,328.19 kg ha-1, to be obtained with the application of 1,522.64 kg ha-1 of NPK and 34.69 mL L-1 of RC. Higher doses of NPK favored an increase in the efficiency of water use, reaching the maximum value of 8.1 kg m-3 with the application of a dose of 1740 kg ha-1. Chapter three presents the costs of production of sweet potato in Serra da Ibiapaba, in addition, simulations of added value and farmer income were carried out for a family production unit that wishes to implement an irrigation system. It was found that, on average, to produce 1.0 kg of sweet potato in the period analyzed required a total expense of R$ 0.47. The production of sweet potato in family farming had the main cost of labor (R$ 6,215.00 per hectare). This agricultural activity allows the maintenance of the activity by family farmers who own small properties, ensuring the level of social reproduction under the conditions studied.